Blautia intestinalis sp. nov., isolated from human feces. Issue 9 (21st September 2021) - Wang, Yu-Jing; Abdugheni, Rashidin; Liu, Chang; Zhou, Nan; You, Xin; Liu, Shuang-Jiang
Abstract : A strictly anaerobic bacterial strain (27-44 T ) was isolated from a stool specimen from an autistic child collected in PR China. The strain was Gram-stain-positive, non-motile, non-pigmented, non-spore-forming, and cells were oval to rod-shaped. Strain 27-44 T grew at 20–40 °C (optimal at 37 °C) and at pH 6.0–10 (optimal at 6.0–8.0). The major polar lipids were one phospholipid, two glycolipids, two aminophospholipids and one unidentified lipid. The major cellular fatty acids of strain 27-44 T were C16 : 0 and C17 : 0 2-OH. The end product of glucose fermentation was mainly butyric acid. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain 27-44 T was a member of the genus Blautia and phylogenetically closely related to Blautia obeum ATCC 29174 T (with 97.8 % seque nce similarity). The genome of strain 27-44 T was 3.5 Mbp with a DNA G+C content of 42.36 mol%. A total of 3436 genes were predicted and, of these, 3133 genes were annotated by KEGG. On the basis of phenotypic, chemotaxonomic and phylogenetic comparisons, strain 27-44 T represents a novel species within the genus Blautia, for which the name Blautia intestinalis sp. nov. is proposed. The type strain is 27-44 T = CGMCC 1.5285 T =NBRC 113774 T .